An assessment of the European Patient Summary for clinical research: a case study in cardiology - Laleci Erturkmen, Gokce Banu; Sinaci, Ali Anil; Namli, Tuncay; Boonstra, Machteld J.; Lekadir, Karim; Gkontra, Polyxeni; Chronaki, Catherine; Facile, Rhonda; Baker, Rebecca; Kush, Rebecca (Frontiers in Medicine, 2024)
The European Health Data Space initiative was launched to create a unified framework for health data exchange across Europe. Central to this initiative is the European Electronic Health Record Exchange Format, designed to achieve interoperability of electronic health record data across Europe. Despite these advancements, the readiness of current guidelines and implementations, such as the European Patient Summary, to support secondary use in clinical research, particularly in cardiology, remains under-explored.Methods: This study aims to evaluate the European Patient Summary guidelines and their implementations, specifically the HL7 FHIR International Patient Summary Implementation Guide, to determine their suitability for secondary use in clinical research. The focus is on identifying gaps and extensions needed to enhance the utility of the European Patient Summary for building artificial intelligence models for assisting heart failure management.We have selected two European Union funded research projects, DataTools4Heart and AI4HF that aim to reuse electronic health record data to develop artificial intelligence models for personalized decision support services for heart failure patients. We analyzed their clinical use cases and the specific data items required, and we compared these with the current European Patient Summary guidelines and provided a detailed gap analysis indicating similarities and required extensions. In our gap analysis, we also compared the needs of DataTools4Heart and AI4HF with the HL7 FHIR International Patient Summary Implementation Guide, to assess the extensions needed to support clinical research.The EHDS is a transformative initiative aimed at establishing a European health data ecosystem that supports both healthcare delivery and clinical research. Our comparative analysis demonstrates that, with minor extensions, these guidelines have significant potential to facilitate access to electronic healthcare record data for secondary uses, particularly in training AI models. We advocate for the adoption of an international patient summary format as a semantically interoperable core set of data elements, which will enhance global clinical research efforts and improve patient outcomes through precision medicine.